Communication technology and social life: Transformation and continuity, order and disorder. (1st June 2014) - Marshall, Jonathan Paul; Notley, Tanya
<x xml:space="preserve">Abstract</x> Anthropology is now developing and using ethnography to research uses and experiences of digital communication technology (including mobile phones, the internet and software), in and across many different cultures and societies. Ethnography enables a focus on the complex intertwining of society, culture and technology allowing us to see how technologies are being transformed by existing modes of life, while simultaneously having a 'messy' influence over those lives, resulting in what are often unexpected consequences. This special issue discusses the use of mobile phones in Papua New Guinea and along the borders of Haiti and the Dominican Republic; the mixture of phone and internet usage in Central Australia and among the Tongan diaspora in Melbourne; the use of internet based video translation practices focused on West Papuan politics; and the disorder produced by software in work environments in Australia. Collectively, these papers help us to reimagine ethnography and challenge conventional theorising of technology by allowing us to discuss the relationships between communication and power in diverse contexts, opening up opportunities for us to engage with and explore the significance of both order and disorder in technologically mediated social processes.